2010
DOI: 10.1094/cm-2010-0405-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Corn Response to Nitrogen Fertilizer as Affected by Planting Date and Hybrid

Abstract: Producers of the eastern Corn Belt are often forced to either delay corn (Zea mays, L.) planting or replant due to unfavorable early season growing conditions. In these situations producers may decrease N rates due to decreased yield potential or switch to short season hybrids to reduce the risk of frost injury prior to maturity. Hybrids with differing yield potential may have different N requirements, but definitive research to determine the impact of hybrid selection on N response is lacking. Field experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…This is consistent with the results of Lauer et al (1999) who reported that grain corn yields decreased with later planting date. In our study, the increase in yield between the two groups of site-years could be explained by the planting date (Mullen et al, 2010), but other parameters such as soil types, hybrids and weather conditions may be involved (Almaraz et al, 2008;Ziadi et al, 2013;Tremblay et al, 2012;Woli et al, 2016). The EONR for the site-years planted before mid-May ranged from 180 to 237 kg N ha -1 (Table 4).…”
Section: Site Id Yearmentioning
confidence: 59%
See 4 more Smart Citations
“…This is consistent with the results of Lauer et al (1999) who reported that grain corn yields decreased with later planting date. In our study, the increase in yield between the two groups of site-years could be explained by the planting date (Mullen et al, 2010), but other parameters such as soil types, hybrids and weather conditions may be involved (Almaraz et al, 2008;Ziadi et al, 2013;Tremblay et al, 2012;Woli et al, 2016). The EONR for the site-years planted before mid-May ranged from 180 to 237 kg N ha -1 (Table 4).…”
Section: Site Id Yearmentioning
confidence: 59%
“…This suggests that an optimum planting date tends to increase EONR. Knapp and Reid (1981) and Mullen et al (2010) have reported that late-planted corn (late May-early June) in New York had lower grain yields and lower N fertilizer requirements than corn planted in late April/early May. The increase in EONR above the current provincial N recommendation also means that the average yield potential for this group of site-years exceeds the provincial average for which the current recommendations were developed by CRAAQ.…”
Section: Site Id Yearmentioning
confidence: 98%
See 3 more Smart Citations